2022
DOI: 10.1007/s11214-022-00940-0
|View full text |Cite|
|
Sign up to set email alerts
|

Meso-Scale Electrodynamic Coupling of the Earth Magnetosphere-Ionosphere System

Abstract: Within the fully integrated magnetosphere-ionosphere system, many electrodynamic processes interact with each other. We review recent advances in understanding three major meso-scale coupling processes within the system: the transient field-aligned currents (FACs), mid-latitude plasma convection, and auroral particle precipitation. (1) Transient FACs arise due to disturbances from either dayside or nightside magnetosphere. As the interplanetary shocks suddenly compress the dayside magnetosphere, short-lived FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 217 publications
0
4
0
Order By: Relevance
“…Precipitating relativistic electrons deposit most of their energy in the lower (below 80 km) ionosphere (in the D‐region and below, see, e.g., Pettit et al., 2023; Xu et al., 2020). Thus, they cannot directly affect the F/E‐regions where SAPS are formed (e.g., Mishin & Streltsov, 2021; Yu et al., 2022, and references therein). On the other hand, energetic ions, with energy fluxes higher than electron fluxes during this event, will deposit their energy above 100 km, well within the E‐region (Fang et al., 2013; Tian et al., 2023).…”
Section: Spacecraft Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Precipitating relativistic electrons deposit most of their energy in the lower (below 80 km) ionosphere (in the D‐region and below, see, e.g., Pettit et al., 2023; Xu et al., 2020). Thus, they cannot directly affect the F/E‐regions where SAPS are formed (e.g., Mishin & Streltsov, 2021; Yu et al., 2022, and references therein). On the other hand, energetic ions, with energy fluxes higher than electron fluxes during this event, will deposit their energy above 100 km, well within the E‐region (Fang et al., 2013; Tian et al., 2023).…”
Section: Spacecraft Observationsmentioning
confidence: 99%
“…Sub‐auroral polarization streams (SAPS), and their more intense counterpart, sub‐auroral ion drifts (SAID), are often associated with the earthward transport (e.g., substorm injections or enhanced convection) of hot ions, their decoupling from electron motion due to diamagnetic drifts, and the formation of strong polarization electric fields and ionospheric flows (see the review by Mishin & Streltsov, 2021; Yu et al., 2022, and references therein). SAPS/SAID are formed between the inner edge of electron and ion plasma sheet (Anderson et al., 1993; Brandt et al., 2008), close to the plasmapause (see low‐altitude and equatorial statistical observations of SAPS/SAID, in He et al., 2014; Nishimura et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest storm-time RC dynamics and the mesoscale flows the impinge poleward of the duskside RC play a crucial role in creating sub-auroral GICs. Furthermore, Yu et al (2022) identified a modeling gap for integrating different spatial and temporal scales to achieve a comprehensive understanding of the entire system. Our approach can provide observational support to such modeling efforts.…”
Section: Contributions and Future Workmentioning
confidence: 99%
“…Recent studies highlight some progress in studies of magnetosphere‐ionosphere coupling. Examples include the investigation of ionospheric outflow and its consequential impact on the magnetosphere, as well as the complex interaction between various electrodynamic processes, such as transient field‐aligned currents, mid‐latitude plasma convection, and auroral particle precipitation (Glocer et al., 2009; Yu et al., 2022). Mid‐latitude regions are of particular interest because they are susceptible to space weather disturbances, resulting from magnetospheric dynamics.…”
Section: Introductionmentioning
confidence: 99%